Etika Buzz Marketing dalam Industri Kecantikan: Tinjauan Normatif terhadap Strategi Komunikasi Pemasaran Digital yang Berpengaruh - Aprinawati Aprinawati; Shelyati Shelyati; Tri Mualim; Bambang Irawan; Kharisma Oktaviani; Reza Palupi; Stepanes A Pardede (BADAN PENERBIT STIEPARI PRESS, 2025)
The beauty industry is among the fastest-growing and most competitive sectors globally. In an attempt to gain a competitive advantage, many companies adopt buzz marketing strategies to create product virality and accelerate sales growth. Buzz marketing leverages social media platforms, utilizing influencers, buzzers, and affiliators to spread messages that generate interest and shape positive public perception. While commercially effective, this marketing technique raises significant ethical concerns, particularly regarding the psychological and social pressure imposed on women—the industry's primary consumer base. This study aims to evaluate the contribution of buzz marketing to the beauty industry while critically examining its ethical implications. Using the normative BP3 approach—Intents, Means, and Ends—this research analyzes how the strategy aligns with or violates ethical marketing principles. A qualitative method is employed through literature review and case analysis to support the normative assessment. The findings reveal that although buzz marketing serves legitimate business objectives, the means by which it operates often perpetuate unrealistic beauty ideals and reinforce societal expectations around physical appearance. This has the unintended consequence of contributing to body image dissatisfaction, mental health struggles, and the normalization of exclusionary beauty standards. These effects raise concerns about the ethical integrity of such practices. The study concludes that for the beauty industry to evolve ethically, it must adopt more inclusive and socially responsible marketing practices. Companies are encouraged to shift toward messaging that celebrates diverse appearances, promotes self-acceptance, and prioritizes consumer well-being. Ethical marketing in this context is not only a moral imperative but also a sustainable strategy for long-term brand trust and loyalty.